2011
DOI: 10.1007/s00540-010-1079-y
|View full text |Cite
|
Sign up to set email alerts
|

Lidocaine depolarizes the mitochondrial membrane potential by intracellular alkalization in rat dorsal root ganglion neurons

Abstract: These results demonstrated that lidocaine depolarizes ΔΨm by intracellular alkalization. These results may indicate one of the mechanisms responsible for lidocaine-induced neurotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…Lidocaine has been recognized to induce apoptotic cell death in human neuroblastoma cells (Friederich and Schmitz 2002), and the mitochondrial pathway was recognized to get involved in the lidocaine-induced apoptosis (Johnson et al 2004;Onizuka et al 2010Onizuka et al , 2011Werdehausen et al 2007). Recently, the ER stress has also been confirmed to involve in the lidocaine-induced apoptosis of rat adrenal pheochromocytoma PC12 cells (Hong et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lidocaine has been recognized to induce apoptotic cell death in human neuroblastoma cells (Friederich and Schmitz 2002), and the mitochondrial pathway was recognized to get involved in the lidocaine-induced apoptosis (Johnson et al 2004;Onizuka et al 2010Onizuka et al , 2011Werdehausen et al 2007). Recently, the ER stress has also been confirmed to involve in the lidocaine-induced apoptosis of rat adrenal pheochromocytoma PC12 cells (Hong et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Lidocaine has been indicated to induce morphological changes such as cell axon collapse and cell swelling (Kasaba et al 2003;Onizuka et al 2005) and to promote apoptosis through the mitochondrial pathway (Johnson et al 2004;Onizuka et al 2010Onizuka et al , 2011Werdehausen et al 2007) and even necrosis (Lawrence et al 1966;Onizuka et al 2012;Yagiela et al 1982). And the promotion to apoptosis or necrosis is not associated with the block of voltage-gated sodium channel, which is the main target of lidocaine, for its anesthetic effect.…”
Section: Introductionmentioning
confidence: 99%
“…Besides epidemiological research, extensive rapid accumulation of α-synuclein was reported in swollen axons in brain tissues from cases who died after TBI (Uryu et al, 2007). In experimental animals, TBI can induce the accumulation of α-synuclein (Uryu et al, 2003), neuroinflammatory response (Morales et al, 2005), progressive loss of nigrostriatal dopaminergic neurons (Hutson et al, 2011), and a reduction in tyrosine hydroxylase activity in the striatum (Onizuka et al, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…That is, the toxicity depends not only on the concentration but also on the cell type. In addition, there are several case reports of cell damage (muscle, cartilage) at clinically relevant concentrations12345678. Although toxicity caused by clinically relevant concentrations is rare, it may produce severe complications when it occurs.…”
mentioning
confidence: 99%